Higher Education Fiscal Allocation Gaps in Indonesia: A Comparison between State Universities and Civil Service Universities - Rizky Maulana; Dominicus Savio Priyarsono; Wiwiek Rindayati; Alla Asmara (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Objective: Higher education in Indonesia faces the challenge of dual governance, leading to unequal allocation of state resources between the Ministry of Education and various ministries. The main problem arises when the limited national education budget is disproportionately absorbed by civil service institutions, while students at state universities face the pressure of rising tuition fees. Method: This study uses a descriptive-qualitative approach in a policy analysis framework to evaluate budget allocations between State Universities (PTN) and Civil Service Universities (PTK). The analysis focuses on calculating unit cost disparities and assessing the impact of dual governance on fiscal equity. Results: The findings indicate a disparity in asymmetric fiscal support, with the average unit cost per student at Civil Service Universities (PTK) reaching Rp26,56 million per year, 1,78 times that at State Universities (PTN) at Rp14,88 million. This inequality is exacerbated by institutional redundancy, including the establishment of general study programs at PTK identical to those at State Universities (PTN), as well as the provision of comprehensive facilities that cover both tuition fees and living expenses exclusively for PTK students. The analysis shows that this budgeting system fails to meet the principles of distributive justice, as the large allocation to PTK does not provide broad benefits to the groups most in need of support, namely state university students burdened by rising UKT (tuition fees).  Novelty: This study recommends reintegrating PTK governance into the ministry responsible for education, allowing the other technical ministry to focus on its core governmental functions. National cost standardization is urgently needed to eliminate casteism in the higher education system and ensure a more inclusive distribution of budget resources for all.